The Wa'a Rai Siwe Tradition in the Perspective of Legal Pluralism: Dialectics of Customary Law, State Law, and Islamic Law in the Bima Society - Yadi Darmawan; Roibin Roibin; Toriquddin Toriquddin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study examines the Wa'a Rai Siwe tradition in the Bima community as a form of customary marriage that continues to be practiced despite the development of national and Islamic law. The tradition raises legal concerns because it potentially conflicts with state law and Islamic legal principles while remaining legitimate under customary law. This study aims to identify the factors contributing to the persistence of the Wa'a Rai Siwe tradition and to analyze it from the perspective of legal pluralism. An empirical legal research method with a descriptive qualitative approach was employed. Data were collected through in-depth interviews with customary leaders, religious leaders, and community members in Tumpu Village, Bolo District, Bima Regency, complemented by documentation and relevant literature. The data were analyzed thematically to identify patterns and interactions among the existing legal systems. The findings reveal that Wa'a Rai Siwe follows a structured process, beginning with the couple's elopement and culminating in customary deliberation (mbolo ra dampa), which generally leads to marriage. The continuity of this tradition is influenced by parental disapproval, high dowry demands, the couple's desire for immediate marriage, and social circumstances such as premarital pregnancy. From the perspective of legal pluralism, the practice reflects the interaction between state law, customary law, and Islamic law. State law regards the practice as potentially violating marriage procedures, while Islamic law considers it inconsistent with the principles of guardianship (wali) and Islamic moral values. In contrast, customary law recognizes Wa'a Rai Siwe as a mechanism for conflict resolution and the preservation of family honor. This study identifies a phenomenon of normative compromise through legalization at the end of the process, whereby a practice initially inconsistent with state and Islamic law ultimately gains legal legitimacy through a valid marriage contract. These findings demonstrate that Wa'a Rai Siwe represents a dynamic manifestation of legal pluralism, with customary law functioning as a living law that continuously negotiates with state and Islamic law to obtain formal recognition.